MEASURING WHAT MATTERS: MEANINGFUL OUTCOMES FOR SCHOOL-BASED SPEECH LANGUAGE THERAPY - Cahill, Peter (My University, 2023)
Outcomes are critical for informing evidence-based, shared decision-making about health supports for children. These outcomes should be important and meaningful to all interested parties, particularly to children and their families, and should be included within research and practice. The work in the present manuscript represents three studies that 1) investigated how service outcomes were being used in school-based, speech-language therapy 2) explored what service outcomes were meaningful and important according to interested parties, and 3) identified a set of core service outcomes using the aggregate input of the interested parties to guide future research and practice. In the first study, I analyzed interview transcripts from 24 senior, school-based speech-language therapists and clinical managers to explore how clinicians working in schools determined the impact of their services. I identified seven outcomes and common facilitators and barriers to the meaningful use of outcomes to determine service impact through this qualitative analysis. In the second study, I interviewed 14 school-based speech-language therapists, teachers, and family members of children receiving supports. I asked participants to speak to the outcomes or impacts of these services they thought were most important or valuable. I identified six outcomes using both qualitative and quantitative analysis techniques. In the third study, I combined the perspectives of these three groups of interested parties into a single set of core outcomes for school-based, speech-language services. The result is a suggested set of impacts to include in research and practice. Including these core outcomes in research will improve the relevance of clinic-external evidence (research studies), providing more pertinent information to shared decision making about speech-language supports in schools. Their inclusion in clinical practice with strengthen clinic-internal evidence (data about specific programs or services) about the appropriateness of supports in context, and will assist the development of local, contextualized evidence for speech-language services.
Keywords: speech-language therapy, speech-language pathology, children, schools, outcomes